2005
DOI: 10.1016/j.ydbio.2005.06.019
|View full text |Cite
|
Sign up to set email alerts
|

The control of morphogen signalling: Regulation of the synthesis and catabolism of retinoic acid in the developing embryo

Abstract: We consider here how morphogenetic signals involving retinoic acid (RA) are switched on and off in the light of positive and negative feedback controls which operate in other embryonic signalling systems. Switching on the RA signal involves the synthetic retinaldehyde dehydrogenase (RALDH) enzymes and it is currently thought that switching off the RA signal involves the CYP26 enzymes which catabolise RA. We have tested whether these enzymes are regulated by the presence or absence of all-trans-RA using the vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
102
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(113 citation statements)
references
References 62 publications
11
102
0
Order By: Relevance
“…In this case, one could suggest that Raldh2 in the proximal third of the early limb bud is required only to switch on expression of Cyp26b in the distal cells at st. 51.5 in hindlimbs and st. 52 in forelimbs. Previous studies in chickens have shown that Cyp26b expression is upregulated in the presence of ectopic RA (Reijntjes et al, 2005). Therefore, it would be interesting to determine if Cyp26b expression is delayed or altered when early Xenopus limb buds are treated with RA.…”
Section: Discussion a Proximal-distal Ra Gradient Could Be Present Inmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, one could suggest that Raldh2 in the proximal third of the early limb bud is required only to switch on expression of Cyp26b in the distal cells at st. 51.5 in hindlimbs and st. 52 in forelimbs. Previous studies in chickens have shown that Cyp26b expression is upregulated in the presence of ectopic RA (Reijntjes et al, 2005). Therefore, it would be interesting to determine if Cyp26b expression is delayed or altered when early Xenopus limb buds are treated with RA.…”
Section: Discussion a Proximal-distal Ra Gradient Could Be Present Inmentioning
confidence: 99%
“…Importantly, direct measurement of RA has shown that regions of the developing mouse embryo that express Raldh2 are actively synthesising RA, whereas regions expressing Cyp26 are actively degrading it (Swindell et al, 1999). Therefore, gradients of RA can be envisaged, and the level of RA present in a particular cell at a particular time in development can regulate target gene expression accordingly (Reijntjes et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…These enzymes catalyze the oxidation of RA into a wide variety of metabolites, such as 4-oxo-RA, 4-OH-RA or 18-OH-RA. Whether these metabolites have a biological activity is still controversial (Niederreither et al, 2002;Reijntjes et al, 2005). Even if most studies have focused on the roles of CYP26 proteins during development, it is known that other CYPs, such as CYP2B6, CYP2C8, CYP3A4/5 or CYP2A6, can also catabolize RA (Marill et al, 2000).…”
Section: An Overview Over the Ra Signaling Cascadementioning
confidence: 99%
“…Thus, at least in vertebrates, patterning of the endoderm requires differential RA signaling activity along the AP axis with RA responsive zones (posterior pharynx, anterior gut) and zones not responsive to RA (anterior pharynx, posterior gut) Stafford and Prince, 2002;Wendling et al, 2000;reviewed in Kumar and Melton, 2003;Mark et al, 2004). These RA reactivity zones are created by localized sources of RA in presumptive fore-and midgut and adjacent mesoderm (established by RALDH1, RALDH2, and RALDH3) combined with specific sinks of RA in the pharynx and organ primordia (such as the lung) (established by CYP26A1, CYP26B1, and CYP26C1) Blentic et al, 2003;MacLean et al, 2001;Reijntjes et al, 2005). In addition, localized endodermal expression of different rar paralogs further fine-tunes this RA signaling activity along the AP axis of the developing endoderm (Bertrand et al, 2007;Mollard et al, 2000).…”
Section: Endoderm Patterning and Pharyngeal Developmentmentioning
confidence: 99%
“…However, cyp26a1 mutants in fish and mouse exhibit relatively subtle hindbrain-patterning defects inconsistent with a global role for cyp26a1 in hindbrain patterning Emoto et al, 2005;Kudoh et al, 2002;Sakai et al, 2001). The recent identification of other cyp26 genes has suggested that these may participate in shaping RA responsiveness in the hindbrain Gu et al, 2005;MacLean et al, 2001;Reijntjes et al, 2005;Reijntjes et al, 2004;Sirbu et al, 2005;Tahayato et al, 2003;Taimi et al, 2004;Zhao et al, 2005). Here, we demonstrate that the zebrafish orthologs of mammalian CYP26B1 and CYP26C1 function redundantly with cyp26a1 to pattern the hindbrain, because embryos depleted of all three proteins exhibit a profound posterior transformation of the hindbrain.…”
Section: Introductionmentioning
confidence: 99%